1.25 trillion is still real money: Some facts about the effects of the Federal Reserve's mortgage market investments - Andreas Fuster; Paul S. Willen (Federal Reserve Bank of Boston, 2010)
This paper measures the effects on the primary U.S. mortgage market of the large-scale asset purchase (LSAP) program in which the Federal Reserve bought 1.25 trillion of mortgagebacked securities in 2009 and 2010. We use an event-study approach and measure the movements in both prices and quantities around the initial announcement of the LSAP and subsequent changes to the program. We use a new dataset to document the changes in the menu of rates and points offered to borrowers and show that there was wide dispersion in the rate changes generated by the announcement of the LSAP program, with some borrowers seeing immediate rate reductions of up to 40 basis points and other borrowers confronting rate increases. We show that the LSAP program led to a substantial boost in market activity, with discontinuous increases in searches, applications and originations for refinance mortgages, but not purchase mortgages. Finally, we show that more creditworthy borrowers were significantly more likely to benefit from the improved credit availability.
Keywords: E5; E21; G21; 330; Hypothek; Kreditmarkt; Staatliche Einflussnahme; Kreditpolitik; Asset-backed security; USA